Biogeochemical characteristics of epiphitic lichen Lobaria Pulmonaria of the Barguzin nature reserve (the republic of Buryatia, Russia) - Bolshunova, Tatiana; Rikhvanov, Leonid; Mezhibor, Antonina; Zhornyak, Lina; Baranovskaya, Natalia; Eremina, Ekaterina (Journal of Environmental Engineering and Landscape Management, 2018)
The research is devoted to the investigation of chemical composition of epiphytic lichens Lobaria pulmonaria growing in the territory of the Barguzin Nature Reserve in the Republic of Buryatia (Russia). This reserve is considered as a background area because of its far location from anthropogenic pollution sources. The objective of this research is to assess the chemical composition of lichens of the Barguzin Nature Reserve – one of the background areas in Russia. 9 lichen samples were collected in the summer 2015, in which the concentrations of 67 chemical elements were detected using inductively coupled plasma mass-spectrometry. The research findings were compared with the data for the lichens from the Zabaykalsky National Park and taiga forest in Tomsk region (oil field area). Comparing the reserve area with the taiga area (with anthropogenic load from oil field development), it was detected that the lichens from the Barguzin Nature Reserve had lower concentrations of most chemical elements except Na, Mg, Al, Si, P, K, Ca, and Ti, which contents are 2-16-fold higher in the lichens of the Barguzin Reserve. The concentrations of most chemical elements detected in the lichen samples of the Barguzin Nature Reserve can be used as baseline values while investigating territories with different anthropogenic load.